1996
DOI: 10.1074/jbc.271.49.31384
|View full text |Cite
|
Sign up to set email alerts
|

A Gene for a Novel Zinc-finger Protein Expressed in Differentiated Epithelial Cells and Transiently in Certain Mesenchymal Cells

Abstract: We have identified a novel zinc-finger protein whose mRNA is expressed at high levels in the epidermal layer of the skin and in epithelial cells in the tongue, palate, esophagus, stomach, and colon of newborn mice. Expression in epithelial cells is first detected at the time of their differentiation during embryonic development. In addition, during early embryonic development there is expression in mesenchymal cells of the skeletal primordia and the metanephric kidney which is later downregulated. The expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
321
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(338 citation statements)
references
References 41 publications
13
321
1
1
Order By: Relevance
“…in vivo, KLF4 is essential for maintaining terminally differentiated epithelial cells in the lung, skin and gastrointestinal tract (Shields et al, 1996;Segre et al, 1999;Jaubert et al, 2003;Blanchon et al, 2006;Patel et al, 2006). In cultured cells, KLF4 expression is temporally associated with conditions that promote growth arrest, such as serum deprivation, contact inhibition and DNA damage, and constitutive KLF4 expression inhibits DNA synthesis (Garrett-Sinha et al, 1996;Shields et al, 1996;Stone et al, 2002). g-Irradiation increases KLF4 mRNA levels in a p53-dependent manner and similarly correlates with increased expression of p21 (Yoon et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…in vivo, KLF4 is essential for maintaining terminally differentiated epithelial cells in the lung, skin and gastrointestinal tract (Shields et al, 1996;Segre et al, 1999;Jaubert et al, 2003;Blanchon et al, 2006;Patel et al, 2006). In cultured cells, KLF4 expression is temporally associated with conditions that promote growth arrest, such as serum deprivation, contact inhibition and DNA damage, and constitutive KLF4 expression inhibits DNA synthesis (Garrett-Sinha et al, 1996;Shields et al, 1996;Stone et al, 2002). g-Irradiation increases KLF4 mRNA levels in a p53-dependent manner and similarly correlates with increased expression of p21 (Yoon et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of p53-dependent cell cycle checkpoint target genes following DNA damage include those encoding the cyclindependent kinase inhibitor, p21 WAF1/CIP1 (El-Deiry et al, 1993;Waldman et al, 1995) and 14-3-3d (Hermeking et al, 1997), which lead to arrest at the G 1 /S and G 2 /M boundaries, respectively, in the cell cycle. We previously demonstrated that the gene encoding Kru¨ppel-like factor 4 (KLF4; also called gut-enriched Kru¨ppel-like factor or GKLF) (Garrett-Sinha et al, 1996;Shields et al, 1996) is transcriptionally activated by p53 following DNA damage (Zhang et al, 1998) and causes cell cycle arrest at both the G 1 /S and G 2 /M boundaries (Yoon et al, 2003;Yoon and Yang, 2004). These results indicate that KLF4 is an important factor in mediating the checkpoint functions of p53 following DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…KLF4 belongs to a large family of Kruppel-like activators with zinc-finger DNA-binding domains, recognizing the common GC boxes found in many, if not most, promoters (Kaczynski et al, 2003). Unlike other members of the family, expression is confined to specific tissues, such as the gut, skin and thymic epithelia (Garrett-Sinha et al, 1996;Shields et al, 1996;Conkright et al, 1999).…”
mentioning
confidence: 99%